Types of personality, audit structure and transformational leadership styles moderate the effect of organizational commitments on auditor performance - Suputra, I Dewa Gde Dharma; Widhiyani , Ni Luh Sari (International research journal of management, IT and social sciences, 2020)
The studies population in this study were auditors of the public accounting firm / KAP in the Province of Bali, then the research sample was determined using a purposive sampling method. Furthermore, primary data were collected in the form of respondents' perceptions using a modified questionnaire from previous researchers and tested for compliance with the instrument's validity and reliability test requirements. Then, the collected data were tabulated and analyzed using the Moderated Regression Analysis (MRA) technique through the following stages: classical assumption test, model feasibility test (F test), determination coefficient analysis (Ajd. R2), research hypothesis testing (t-test) is good for its partial and moderate influence. The results of the study found that organizational commitment improves auditor performance. Personality type is not able to strengthen the positive effect of organizational commitment on auditor performance. Audit structure and transformational leadership style reinforce the positive effect of organizational commitment on auditor performance.